"I'm sick of doing nothing:" how boredom shapes rape crisis center volunteers' social movement participation. (4th July 2022) - Weiss, Benjamin R.
ABSTRACT: Extensive research shows that emotions influence social movement participation. Scholars argue that emotions like anger and pride generally activate – i.e. increase movement participation – whereas emotions like hopelessness and sadness generally deactivate. Organizational theory complicates this research by showing that the same emotions can produce varied outcomes, although the causes of variation remain undertheorized. This article brings together these disparate literatures to ask how boredom, an emotion underexplored in the social movement literature, shapes political participation in a rape crisis center. Drawing on three years of participant observation and forty in-depth interviews, the author shows that, while most volunteer victim advocates experience boredom while answering less 'legit' hotline calls and passing time during shifts, their boredom does not necessarily deactivate. Instead, the meaning volunteers attach to their boredom – specifically through a process this article terms 'emotional attribution' – shapes activation. Volunteers who blame their boredom on organizational conditions and service provision models often decrease their participation, whereas volunteers who understand boredom individualistically remain engaged. These findings advance social movement and organization theory by disrupting assumptions about the essential 'good'-ness or 'bad'-ness of emotions, and by theorizing emotional attribution as an interactional process predictive of variation in the consequences of emotions.